Graphene Transfer: A Physical Perspective - Xavier Langston (MDPI AG, 2021)
Graphene, synthesized either epitaxially on silicon carbide or via chemical vapor deposition (CVD) on a transition metal, is gathering an increasing amount of interest from industrial and commercial ventures due to its remarkable electronic, mechanical, and thermal properties, as well as the ease with which it can be incorporated into devices. To exploit these superlative properties, it is generally necessary to transfer graphene from its conductive growth substrate to a more appropriate target substrate. In this review, we analyze the literature describing graphene transfer methods developed over the last decade. We present a simple physical model of the adhesion of graphene to its substrate, and we use this model to organize the various graphene transfer techniques by how they tackle the problem of modulating the adhesion energy between graphene and its substrate. We consider the challenges inherent in both delamination of graphene from its original substrate as well as relamination of graphene onto its target substrate, and we show how our simple model can rationalize various transfer strategies to mitigate these challenges and overcome the introduction of impurities and defects into the graphene. Our analysis of graphene transfer strategies concludes with a suggestion of possible future directions for the field.